Rancang Bangun E-Sertifikat Berbasis Website Dengan Teknologi QRCode Menggunakan Metode Object Oriented Programming (Studi Kasus di Instansi Pendidikan Tinggi XYZ) - Riad Sahara; Raden Muhammad Firzatullah; Albaar Rubhasy; Irfan Nurdiansyah (Fakultas Ilmu Komputer, 2021)
This research will discuss the analysis of the design and manufacture of website-based e-certificate applications using the Object Oriented Programming (OOP) method. The main problems that underlie this research are the waste in the use of paper and the cost of printing certificates, as well as the difficulty of distributing certificates to participants for every activity held in an agency. In addition, another problem is the number of fake certificates from activities that have been held and the difficulty of checking the authenticity of these certificates. Therefore, we need an application that can facilitate the making of certificates without having to be printed conventionally, assist in distributing certificates from activities that have been held to activity participants, as well as in checking the authenticity of certificates. For making applications using the OOP method with tools Unified Modeling Language (UML) as a tool in designing applications. The results achieved from this research are a website-based e-certificate application that will be used to print certificates digitally (paperless), distribute e-certificates from every activity organized by an agency, and check the authenticity of certificates using QRCode technology.